Cook (mageiros) in Byzantium. Was there any Female mageiros? - Anagnostakis, Ilias; Leontsini, Maria (Studia Ceranea, 2022)
The paper studies terms describing cooks and cooking activities that are preserved in Byzantine literature and draw their origins from the ancient Greek literature as well as from biblical and theological texts. Despite some development regarding the preference to the term opsopoios and opsartytēs without ceasing to use the term mageiros for the male cook, as well as the term demiourgos, only the latter is used for women to signal solely the preparation of pastries. It is proved that the conceptualization and connotations of the term mageiros, which are presented in detail, prevented its attribution to women. Further proof on the use of feminised masculine nouns for female professions or occupations in literature and the more concrete evidence on the services recorded in the typika of nunneries display the absolute abiding of the conscious avoidance of the term for women’s involvement in cooking.